PENGENTASAN KEMISKINAN MELALUI PEMBANGUNAN JARINGAN EKONOMI PEDESAAN (Sebagai Suatu Strategi)* - Prijono Tjiptoherijanto (Populasi, 1997)
Various policies have been implemented by Indonesian government in its efforts to eliminate poverty. This paper proposes BKKBN's (National Family Planning Coordinating Agency) attempts which stress on poverty elimination in non-backward area by way of prosperous family development through expanding rural economic network. The program is started with improving movement of "pride of village" through programs of Plaju (that of Harvesting, Processingand Selling), Pemaju (that of Packaging and Selling), and Penguja (that of Services entrepreneurs) followed by Takesra ( that of Savings for People's Prosperity) and Kukesra (that of Entrepreneurial Credit for Prosperous Family). Through the programs, rural families are expected to play roles in agribusiness and agrobusiness sectors, as well as in small-scale industry. With the benefit gotfrom the programs, it is then expexted that levels of families' income increase consequently, and number of poor families in rural areas can be eliminated.